GIANT LIVER FLUKE AND MOOSE: JUST A FLUKE? - Vannatta, J. Trevor; Moen, Ron (Lakehead University, 2017)
The giant liver fluke, Fascioloides magna, is a possible contributing factor to moose(Alces alces) declines in North America, but evidence linking F. magna infection directly to moose mortality is scarce. This review identifies knowledge gaps about the transmission and impact of F. magna infection on moose and proposes new directions for research and management of this parasite. We suggest that the importance of intermediate snail hosts has been largely neglected in current management discussions and warrants greater emphasis. The intermediate hosts responsible for F. magna transmission likely vary by region and recent genetic evidence suggests that F. magna was restricted to several isolated refugia during cervid extirpation events in North America. This distributional history represents several coevolutionary and pathological implications for definitive hosts of F. magna. We suggest that F. magna infections are most ecologically significant as they relate to sublethal impacts and multiple parasitic infections. In assessing infection risk on landscapes, most models rely heavily on monitoring white-tailed deer (Odocoileus virginianus), but this approach only measures risk indirectly. The reliability and accuracy of models would probably improve if snail habitat in ephemeral wetlands was included as a predictor variable.